UAV‐based mesoscale lithologic distribution map of a large shear zone in Jurassic accretionary complex (Ohwaki outcrop in the Mino Belt, central Japan). (15th August 2016) - Yamaguchi, Asuka; Fukuchi, Rina; Hamahashi, Mari; Shimizu, Mayuko
Abstract : A detailed lithologic distribution map based on an orthophotograph was created by aerial photographs taken by an unmanned aerial vehicle (UAV). It shows the occurrence of the 50‐m‐wide shear zone in the Jurassic accretionary complex.